Clinical significance of sensitization to house dust mite allergens using flow cytometry-based basophil activation test - N. V. Bychkova; I. V. Krutikova; A. V. Chernyshova; N. M. Kalinina (Медицинская иммунология, 2022)
Respiratory allergy takes a significant place among allergic diseases. Similar clinical manifestations occur in sensitized patients in response to various airborne allergens. Accordingly, the allergen testing by means of in vivo and in vitro techniques is necessary to identify a causally significant allergen. The main laboratory assay to estimate sensitization to the airborne allergens is based on detection of specific immunoglobulin E (sIgE). However, clinical manifestations cannot be always confirmed by this test. The aim of this work was to evaluate the potential of basophil activation test (BAT) using flow cytometry, in order to confirm sensitization to house dust mite allergens. The BAT was carried out with allergens from Dermatofagoides in 34 volunteers, 130 patients were examined at the Russian Centre of Emergency and Radiation Medicine (33 people with household and 97 people with polysensitization), and 10 patients with allergy to house dust mites confirmed by skin testing. The sensitization was assessed using two laboratory kits (Allergenicity and BD FastImmune). The total IgE and sIgE to house dust mites, as well as concentrations of eosinophilic cationic protein, were determined. Specificity of the BAT with Allergenicity kit for the house dust mites was 94%. The sensitivity was 88% in the patients with household sensitization, thus being comparable with skin testing results available from the literature. An absolute correlation was found between positive results of skin testing and the BAT. In patients with household sensitization, sIgE levels > 0.35 UA/mL were detected in 39% of cases. A positive correlation was shown between the indices of basophil activation in response to testing allergens, and total immunoglobulin E and sIgE concentrations. High degree of correlation was found between the results of Dermatofagoides sensitization testing with both BAT kits. It was shown that the use of H1 histamine receptor blockers had no effect on BAT results. A decrease in sensitivity assay for airborne allergens was revealed upon therapy with glucocorticosteroids. Due to the proven clinical significance of the basophil activation test for diagnosing sensitization to inhaled allergens, one may require to supplement the range of approved assays in Russian Clinical Guidelines with BAT testing to prove sensitization in patients with allergic rhinitis and bronchial asthma, thus contributing to better diagnosis of causally significant allergens and, accordingly, administration of proper therapy.